2022
DOI: 10.1111/jfbc.14154
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of salicylic acid and calcium chloride delays the loss of chlorophyll and preserves the quality of broccoli during storage

Abstract: Consumer awareness of broccoli's unusual color, rich flavor, and concentration of desired phytochemicals has led to a steady increase in consumption in recent years. However, its short shelf‐life, which is linked with quick discoloration and degeneration after harvest, limits industrial production and marketing. The effect of pre‐harvest salicylic acid (SA) and calcium chloride (Ca) and their combination on the post‐harvest quality of broccoli during storage (5 ± 1°C) was explored in this study. The foliar spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In the study by Alali et al (2023), it was observed that citric acid has the ability to close stomata, decrease transpiration rates, and mitigate weight loss in fruits and vegetables. Similarly, research conducted by Eleni and Theodoros (2011), Babu et al (2014) and Rastegar et al (2022) highlighted the anti-aging properties of CA, SA, and PUT, which also proved beneficial in reducing weight loss in vegetables by scavenging reactive oxygen species and preserving membrane integrity. Mustafa et al (2018a) reported that SA treatment is important for the degree of inhibition of the metabolic activity of the fruit and that 1 mM SA treatment delayed weight loss in mangosteen after 14 days of storage.…”
Section: Storage Duration (Sd)mentioning
confidence: 84%
See 3 more Smart Citations
“…In the study by Alali et al (2023), it was observed that citric acid has the ability to close stomata, decrease transpiration rates, and mitigate weight loss in fruits and vegetables. Similarly, research conducted by Eleni and Theodoros (2011), Babu et al (2014) and Rastegar et al (2022) highlighted the anti-aging properties of CA, SA, and PUT, which also proved beneficial in reducing weight loss in vegetables by scavenging reactive oxygen species and preserving membrane integrity. Mustafa et al (2018a) reported that SA treatment is important for the degree of inhibition of the metabolic activity of the fruit and that 1 mM SA treatment delayed weight loss in mangosteen after 14 days of storage.…”
Section: Storage Duration (Sd)mentioning
confidence: 84%
“…( 2014 ) and Rastegar et al. ( 2022 ) highlighted the anti‐aging properties of CA, SA, and PUT, which also proved beneficial in reducing weight loss in vegetables by scavenging reactive oxygen species and preserving membrane integrity. Mustafa et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indicators of the heat stress response include photosynthetic responses, antioxidant enzyme activities, cell membrane integrity [19], and the content of osmotic substances. It has been shown that exogenous Ca 2+ increased the heat tolerance of Arabidopsis [20] and Rhododendron [21], which might be associated with altering carbohydrate metabolism [22], delays the loss of chlorophyll [23], higher antioxidant enzyme activities [24], and decreased electrolyte leakage [25]. However, excessive Ca 2+ concentration might be cytotoxic [24], and the optimal concentration of Ca 2+ needs further experiments.…”
Section: Introductionmentioning
confidence: 99%